Reaching for customer centricity: Wine brand positioning configurations - Marc Dressler; Ivan Paunovic (Journal of Open Innovation: Technology, Market, and Complexity, 2021)
This study set out to uncover brand positioning configurations by presenting state-ofthe- art brand management literature and applying a novel, mixed-methods approach to examine the under-researched wine industry transformation towards open innovation in branding. German winery brands were analyzed using a multimethod approach leaning on a novel netnographic methodology and multiple sources. The sample included 572 wineries from all 13 German wine regions with website text data and online review text data from each winery. The study identified nine prime words used to describe both brand identity as well as wine brand image. It revealed word-price clusters of brand identity and image. The results offer insights into communication and pricing opportunities for wine brand identity as well as image, thereby contributing to open brand innovation.
Keywords: 650; open innovation; web scraping; wine branding; wine marketing; digital marketing; netnography; grounded theory; classification; online communication; brand identity; brand personality; brand image